Tradisi Mappakatanni dalam Muamalah: Studi Terhadap Pemahaman Konsep Riba Masyarakat Desa Parinding - Ronny Mahmuddin; Aswar Aswar; Ridwan Ridwan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2021)
This research aims to find out the understanding of the people of Parinding Village of Baraka Subdistrict about usury in economic activity. The study focused on the understanding of the Parinding Village community about the law of borrowing money in conventional banks, garden/rice field pawns (mappakatanni), and buying and selling motor loans through conventional financing institutions. Research methods apply the type of field research with sociological and normative approaches. The results show that there are still many people who do not know about the nature of usury. They consider that riba is taking an extra too high in receivable debt, for example that done by loan sharks, while if the addition is taken from a small loan then it is not riba. In buying and selling people do not understand riba, as well as in garden/paddy fields (mappakatanni) and motor loans, which they know that riba is only found in receivable debts that take additional loans and they exemplify as conventional banks do.